Posterior dynamic stabilization in the lumbar spine – 24 months results of a prospective clinical and radiological study with an interspinous distraction device - Daentzer, Dorothea (BMC Musculoskelet Disord, 2016)
BACKGROUND: Interspinous distraction devices (IDD) are due to maintain or restore intersegmental range of motion (iROM) in a controlled fashion with the aim of stabilization the affected level dynamically. The following study is the first to present clinical and radiological data with the Wallis® spacer during a follow-up of 24 months. METHODS: Ten patients underwent posterior dynamic stabilization (PDS) of the lumbar spine with an IDD (Wallis® spacer) and were controlled clinically and radiologically after 3, 6, 12, and 24 months in a prospective study design. Pain intensity, functional disability and life quality were assessed by use of subjective scores. Motion analyses were performed with the help of lateral functional x-rays to determine the iROM of the operated segments and total ROM (tROM) of the lumbar spine. In addition, roentgen stereophotogrammetric analysis (RSA) was used to measure the iROM of the treated levels. RESULTS: During the postoperative course pain and disability most clinical scores were significantly improved. After 24 months we observed statistically significant reduction in back pain intensity with a mean value of 6.0 on visual analog scale (VAS) before surgery and of 2.7 at the latest evaluation. The leg pain was also decreased without statistical significance from 4.7 preoperatively to 2.1 at final follow-up. The functional disability according to Oswestry Disability Index (ODI) and Roland-Morris Disability Questionnaire (RM) was decreased both with statistical significance at all examination dates with a mean value in ODI of 40.0 % before operation and of 17.3 % after 2 years and an initial mean value in RM of 55.2 and of 23.5 % after latest follow-up. After 24 months, the results of the health related quality of life score also showed much better values with only two exceptions. The iROM of the treated levels was reduced during each follow-up examination with preserved residual mobility. Directly postoperatively and after 3 and 12 months intersegmental mobility was statistically significantly decreased with an average iROM of 6.62° before operation and of 2.69° few days after surgery, of 3.79° and 3.16° 3 and 12 months later. At 6 (4.37°) and 24 (4.01°) months follow-up iROM was also but not statistically significantly reduced. The mean tROM did not change significantly during all postoperative controls. CONCLUSIONS: The radiological findings support the thesis of posterior dynamic stabilization by the used implant. The positive clinical findings should be interpreted with caution because of the limited number of patients and the missing control group.